The Impact of Paulownia Leaves Extract on Performance, Blood Biochemical, Antioxidant, Immunological Indices, and Related Gene Expression of Broilers - Sakr, Shimaa A.; EL-Emam, Huda A.; Naiel, Mohammed A. E.; Wahed, Noha M.; Zaher, Hanan A.; Abougabal, Mohammed Sh.; Alghamdi, Youssef S.; Albogami, Sarah; Soliman, Mohamed Mohamed; Shukry, Mustafa; Elghareeb, Mona M. (Frontiers in Veterinary Science, 2022)
The current research sought to assess the effects of paulownia leaves extract (PLE) on performance, blood hematological, antioxidant activity, and immunological response of broiler chicken. In total, two hundred 1-day-old male Cobb500 chicks were allocated randomly into four equal treatments with 5 replicates. The first treatment served as a control (CNT) and was fed the basal diet only, while the other treated treatments were fed on the basal diet supplemented with 0.1, 0.3, and 0.5 g/kg diet of PLE, respectively. The performance results showed significant increments (P < 0.05) in live body weight (LBW), weight gain (WG), and European production efficiency factors (EPEIs) (linearly; p < 0.001) in cooperated with increasing PLE levels in broiler diets. At the same time, feed conversion ratio (FCR) and livability percentages were numerically enhanced under the effects of PLE supplementation. Moreover, a notable increase (P < 0.05 or 0.01) in oxidative remarks activity (GSH, glutathione; SOD, super oxide-dismutase and CAT, catalase) and elevated levels of immunoglobulin (IgM, immunoglobulin M and IgG, immunoglobulin G) were noted (P < 0.05) for treatments fed with PLE in a dose-dependent manner. Also, a dramatic linear increase was observed in mRNA expression of IGF-1, GHR, IL-1β, and IL-10 genes of broiler chickens. This study concluded that enriched broiler feeds with 0.5 g/kg PLE might be a beneficial strategy to promote broiler health and production.